2014
DOI: 10.1002/eji.201343680
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated STAT3 and PD‐1 regulate IL‐17 production and IL‐23 receptor expression in Mycobacterium tuberculosis infection

Abstract: SUMMARY We studied the factors that regulate IL-23 receptor expression and IL-17 production in human tuberculosis infection. Mycobacterium tuberculosis (M. tb)-stimulated CD4+ cells from tuberculosis patients secreted less IL-17 than did CD4+ cells from healthy tuberculin reactors (PPD+). M. tb cultured monocytes from tuberculosis patients and PPD+ donors expressed equal amounts of IL-23p19 mRNA and protein, suggesting that reduced IL-23 production is not responsible for decreased IL-17 production by tuberculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 58 publications
3
37
2
1
Order By: Relevance
“…Programed death ligand-1 signals via PD-1 on CD4 + T cells, and recently it was reported that Mycobacterium -induced PD-1 coordinates suppression of Th17 response in tuberculosis patients (28). We confirm that M. tuberculosis significantly enhances the frequency of PD-1 + T cells in the DC/monocyte–CD4 + T cell cocultures (Figures 7A,D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Programed death ligand-1 signals via PD-1 on CD4 + T cells, and recently it was reported that Mycobacterium -induced PD-1 coordinates suppression of Th17 response in tuberculosis patients (28). We confirm that M. tuberculosis significantly enhances the frequency of PD-1 + T cells in the DC/monocyte–CD4 + T cell cocultures (Figures 7A,D).…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports in tuberculosis patients indicate that active disease and its severity are associated with low Th17 response (26, 27). Of note, anti-tuberculosis therapy is associated with enhanced Th17 response, suggesting that M. tuberculosis suppresses Th17 response as one of the immune evasion mechanisms (28). …”
Section: Introductionmentioning
confidence: 99%
“…(13). This was a surprising finding given that no such defect or infectious predilection is seen in AD-HIES despite the impaired capacity for RORγt upregulation(14). This observation might be partially explained by the recent finding that while unconventional T cells (which could have roles in anti-mycobacterial immunity) such as natural killer T cells (NKT cells) and mucosal-associated invariant T cells (MAIT cells) are reduced in AD-HIES, the MAIT at least express normal levels of ROR γt(15).…”
Section: Introductionmentioning
confidence: 98%
“…A causal relationship between PD-1 signaling and IL-17 response is suggested by the fact that tuberculosis patients were found to have increased numbers of PD-1+ T-cells compared with healthy individuals, and in this case, CD4+ T-cells secreted less IL-17 [195]. Overall, PD-L1 deficiency or blockade is suggested to play an important role in Th17 expansion, and the PD-L1/Th17 axis may be an important therapeutic target for cancer treatment.…”
Section: Rationale For Combined Anti-pd1 and Anti-il-23/il-17 Treatmentmentioning
confidence: 99%